Slovenska podjetja in družbena odgovornost: Slovenski podjetniški observatorij 2016 - Močnik, Dijana; Crnogaj, Katja; Bradač Hojnik, Barbara (University of Maribor Press, 2017)
Slovenian Companies and Corporate Social Responsibility : Slovenian Entrepreneurship Observatory 2016. In first chapter, we first analysed all companies and entrepreneurs in Slovenia for the year 2015, then we compared for the year 2013 key data of the EU-28 and Slovenia in the non-financial business economy (the activities of industry, distributive trades and services). In Slovenia, 127,373 businesses employed 532,325 people in 2015. The manufacturing sector also generated the largest value added (7.4 billion euros) and exports (16.6 billion euros). In second chapter, we examined the context of corporate social responsibility on the company and national levels in Slovenia and the EU, involving different business practices, initiatives and actions, with the goal of contributing to the society and environment in which companies function. We found that the supportive environment for corporate social responsibility in Slovenia is well-developed, but there is a lack of cooperation and integration towards a common concept of social responsibility on the national level. We also show the state of socially responsible behaviour of companies and analyse their practices and initiatives.